Internal and External Barriers to Help Seeking: Voices of Men Who Experienced Abuse in the Intimate Relationships - Lysova, Alexandra (International journal of offender therapy and comparative criminology, 2022)
This qualitative study explores internal and external barriers to help seeking among 41 men from four English-speaking countries who self-reported victimization from a female intimate partner. Twelve online focus groups were conducted and themes were identified inductively at a semantic level. Six identified themes represented four internal (blind to the abuse, maintaining relationships, male roles, and excuses) and two external barriers to help seeking (fear of seeking help and nowhere to go). Most participants who avoided seeking help did so due to their own lack of recognition of abuse and ability to assess their risk of harm, attempts to keep the family intact, masculine stereotypes, and excuses for their partner’s abuse. Some men who expressed an interest in seeking help were discouraged from it due to fear for their personal safety, a potential revictimization in the legal system, and the lack of support services available to men. This research suggests that the individuals who are abused in relationships, service providers, and the public at large could benefit from professional training about gender inclusive approaches to intimate partner abuse.